With every breath - Kurland, Lynn.; Copyright Paperback Collection (Library of Congress) (New York : Jove Books, 2008)
When medieval laird Robert Cameron pounds on Sunny Phillips's door, he isn't paying a social call. He's braved a trip onto enemy soil to fetch the MacLeod witch, a crone renowned for her healing powers. But the woman who opens her door to him is enchanting and young... and not from his century.
Keywords: Time travel-fiction